Atıksu Arıtma Tesisleri İçin Uygun Alanların Cbs Destekli Çok Ölçütlü Karar Analizi Yöntemi İle Belirlenmesi - Yücel, Uğur (Fen Bilimleri Enstitüsü, 2015)
Günümüzde ilçeler, kentler gibi yerleşim alanları hızlı bir şekilde büyümekte ve gelişmektedir. Bu ilçeleredeki gelişmenin kontrolü, çalışmaların ekonomik, iyi koşullarda yapılabilmesi, yaşayan insanların ihtiyaçlarının tespit edilmesi ve planlanması için bilgi sistemlerine gün geçtikçe daha çok ihtiyaç duyulmaktadır.  Atıksu arıtma tesisilerinin kurulması modern şehirleşmede önemli bir yer tutmaktadır. Bu tesislerin yerlerinin belirlenmesi; şehir yaşanırlığı, çevrenin temiz olması ve atık suların tekrar doğaya temiz bir şekilde geri dönmesi açısında önemli bir faktördür. Bu çalışmada, Kayseri ili Sarıoğlan ilçesi için halihazır haritası, imar planı kullanılarak ilçeye yapılacak olan atıksu arıtma tesisinin yerinin en uygun şekilde belirlenebilmesi için Analitik Hiyerarşi Yöntemi (AHY) kullanılarak, Coğrafi Bilgi Sistemi (CBS) ortamında bir Çok Ölçütlü Karar Analizi (ÇÖKA) modeli oluşturulması amaçlanmıştır.  Sarıoğlan ilçesi; güneyinde Bünyan, doğusunda Akkışla, batısında Özvatan ilçeleri ve kuzeyinde Sivas ili bulunmaktadır. Kayseri’nin küçük ilçelerinden biri olan Sarıoğlan’ın 2014 yılı adrese dayalı nüfus kayıt sistemine göre nüfusu 14.521 kişidir.  Türkiye’deki kanalizasyon, yağmur suyu tahliyesi ve atık su arıtma tesisi projelerinin hazırlanması ve inşaatı konusunda deneyimli ve aktif bir kamu kurumunda çalışan 2 müdür ve 5 teknik uzmanın görüşleri alınarak atıksu artıma tesislerinin yapılacağı yerler belirlenirken en önemli 8 adet ölçüt belirlenmiştir. Aynı kurumun çalışanlarının katıldığı bir anket çalışması yardımıyla ölçütlerin ikili karşılaştırmaları yapılarak ağırlıkları belirlenmiştir. Belirlenen ağırlıklardan; düşük kotlu arazi, imar alanlarına uzaklık, kamulaştırma, meskuna uzaklık ve ulaşım yollarına yakınlık ölçütlerinin ağırlıkları diğer ölçütlere göre daha yüksek olduğu görülmüş olup analiz sırasında bu ölçütlerin daha baskın geldiği görülmüştür. Çalışmadaki verilerin aynı kapsamda analiz edilebilmesi için bazı ölçütlerin en büyük değeri 1, bazı ölçütlerin ise en büyük değeri 0 olacak şekilde normalleştirme yapılmıştır. Normalleştirme işlemi sonucunda ölçütlerin değerleri 0 ile 1 arasında olacak şekilde belirlenmiştir. Tüm ölçütler belirlenen ağırlıklarıyla beraber CBS yazılımı yardımıyla birleştirilmiş, analiz sonunda ortaya çıkan sentez haritası yeniden normalleştirilmiş,  uygun analizi sonuçlarına göre 9 farklı bölüme ayrılmış ve arıtma tesisinin yapılabileceği en uygun alanlar belirlenmiştir. Belirlenen alan yaklaşık 33 hektar olarak hesaplanmıştır.

In our days residential areas like counties and cities are growing and developing expeditiously. Thereby to control the development constructionally and economically in the residential areas, specifying and planning the needs of residents, information systems are needed gradually. A significant increase in environmental problems in our country in recent years. Rivers, lakes and marine waters contaminated waste next to the threatening situation has come to vibrant health. Especially in the areas of migration cities and towns it has been large-scale population growth. Uncontrolled sewage discharges are a result of population growth and development in addition to industrialization. This situation gives serious damage to the environment. Plants such as environmental pollution caused by the death of the living being also affected negatively and cause economic losses. Increasing environmental problems in our country has led to increased sensitivity on this issue. After disposing of the waste water that holds an important place in terms of the environment and has rendered harmless discharge on the agenda. Therefore, the existing water source pollution to water sources and wastewater treatment is required for more efficient use. Establishment of waste water treatment has a great role in modern urbanizing. Locating the treatment facilities is an important factor for city inhabitability, clean environment and waste waters’ oscillation to the nature. The first wastewater treatment plant in the modern sense in the world was founded in Hamburg in 1842. The start of the construction of treatment plants after 1870. It is only passed from the date of the present number of 15,000 wastewater treatment plants in the United States. Last time in have been great advances in technology and treatment techniques, but also changed the concepts and principles related to environmental regulations. Construction of the treatment plant, a process that began with the completion of the work on planning and design. Proper selection and design of process, site selection, after the completion of the transactions, such as making ground surveys of selected land to the construction process begins with the establishment of the treatment plant site. There are many factors in planning the construction of treatment plants. On the other hand, the siting of a residential treatment facility is quite complex and involving many disciplines. Therefore, in addition to a number of factors in determining the spatial extent of the location of the treatment plant it must be taken into consideration as well. It is possible to determine the location of the treatment plant with a lot of information system and analysis. The most important of Geographic Information System used in many urban problems (GIS) and the Multi-Criteria Decision Analysis are studies using together. Today, using GIS and analytic hierarchy process along; land suitability analysis, energy management, risk analysis, marketing, management of groundwater resources, the personnel selection made mobile information system design in technology selection and work among the candidates who applied and received an application become referenced in this similar to many areas.. In this study, to locate the most appropriate area for waste water treatment plant for Sarıoğlan County in Kayseri Province, Analytical Hierarchy Method (AHM) was used on Geographical Information System (GIS) platform and aiming to constitute The Multiple Criteria Decision Making model. Determining the right place before the wastewater treatment plant; the cost is an important factor in terms of the plant during operation and the efficiency is low. A multi-criteria decision analysis application will increase the accuracy of the analysis to be made of current data. These methods include studies to be carried out without the idle will be possible to give you years of service. For this purpose, given the work carried out in general using AHP and attempted to establish a view on how it is applied in different areas of the chosen method. GIS concept, historical development, tasks were addressed to the field of application and benefits. GIS and Multi-Criteria Decision Analysis of the relationship, identifying the existing problems, the modeling of decision analysis, to determine the extent, normalization, emphasizing the determination weight. AHP is available with both objective and subjective evaluation criteria. Criteria can be seen from the assessment of whether it is consistent. At the same time, the weights of the criteria determined by the binary comparison, when another new measure of weight added or changed substantially different results may be removed when the current measure. Sarıoğlan County’s neighboring settlements are Bünyan to the south, Akkışla to the east, Özvatan and Sivas to the North. Also Sarıoğlan is one of the smallest counties of Kayseri Province and its population is 14.521 for 2014 according to the Address Based Population Registration System. Sarıoğlan County, 65 km from Kayseri, Sivas is 130 km away. County established the  Sarioğlan Valley takes its name here. There are 1150 m above mean sea level. Locating the optimum areas for waste water plantations, 8 most important criterion have been determined. In this way, 2 managers’ and 5 technical experts’ opinions who have experience in sewerage systems, rainwater disposal systems and wastewater treatment plants and working actively in public corporation have been received. By means of a survey which was attended by employees of the same corporation criteria weights are determined by making binary comparisons. From determined weights, the low elevation, distance to the urban area, expropriation, the weights of the criteria of distance to residential and proximity to the roads found to be higher than other measures during the analysis have been seen more dominant of these criteria. For analyzing the data in study to the same extent the maximum value of some criteria is 1, and for some measure of the maximum value is normalized to be 0. As a result of the normalization process values of the criteria are determined to be between 0 and 1. All criterion combined by help of ArcGIS with their designated weights, synthesis map is normalized again that came off in the end of the analysis, divided into 9 sections and determined the most appropriate area of the treatment plant can be made.  As a result, the county's height information of the land, construction, agricultural and residential areas, transportation and power lines, have been informed about the water bodies and sources and how it is seen to affect the location of the extent of the treatment plant. Criteria specified weights of all the eligible regions of the wastewater treatment plant south of the town on the map emerged when combined reference may be made and it is seen that the most appropriate area of 33 hectares.
Determining Suitable Areas For Wastewater Treatment Plant Using Gis Based Multicriteria Decision Analysis Method
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2015
Keywords: Çok Ölçütlü Karar Analizi; Cbs; Ahy; Gis; multi-criteria Decision Analysis; Ahp